Green Recruitment and Rewards, Environmental Training, and Pro-Environmental Behavior: Evidence from Conservation Organizations in South Kalimantan - Sudarwati; Rini Rahmawati; Ahmad Rifani (Citakonsultindo, 2025)
This study investigates the influence of Green Human Resource Management (GHRM) practices namely Green Recruitment and Green Rewards on Pro-Environmental Behavior (PEB), with Environmental Training as a mediating variable, within the Ability-Motivation-Opportunity (AMO) framework. Using a cross-sectional survey of 100 employees from conservation organizations in South Kalimantan, Indonesia, and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), the results demonstrate that both Green Recruitment and Green Rewards significantly enhance Environmental Training, which in turn strongly predicts PEB. Furthermore, Environmental Training partially mediates the relationships between GHRM practices and PEB, emphasizing its central role in operationalizing environmental values into workplace behaviors. The study contributes to the literature by validating the AMO model in a non-corporate, conservation-focused context in the Global South and offers practical insights for sustainability-oriented HR strategies.